1982
DOI: 10.1159/000287620
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Verbal Expression in Psychosomatic and Psychoneurotic Patients

Abstract: Psychopathology and verbal expression were investigated in 20 psychoneurotic patients and 20 psychosomatic patients (10 patients with ulcerative colitis and 10 patients with Crohn’s disease). The Crohn’s disease patients showed as much psychopathology as the psychoneurotic patients, but the ulcerative colitis patients showed significantly less psychopathology. However, the Crohn’s disease and ulcerative colitis patients showed a similar reduction in verbal-emotional expression (alexithymia), when they were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…As Taylor and Doody [17] found in a study using projective test measures, the UC patients showed a similar level of alexithymia as the CD patients. The findings that alexithy mia scores were not significantly correlated with level of disease activity and duration of illness suggest that alexithymia is related to the disease per se, rather than being a reaction to clinical activity or illness duration.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As Taylor and Doody [17] found in a study using projective test measures, the UC patients showed a similar level of alexithymia as the CD patients. The findings that alexithy mia scores were not significantly correlated with level of disease activity and duration of illness suggest that alexithymia is related to the disease per se, rather than being a reaction to clinical activity or illness duration.…”
Section: Discussionsupporting
confidence: 65%
“…Indeed, in a study comparing alexithymia in IBD patients and psychoneurotic patients, Taylor et al [ 16] found unacceptable interrater agreement on the BIQ and no significant difference in the mean BIQ scores of the two patient groups. Nonetheless, using projective test measures, Taylor et al [16][17][18] did find that IBD pa tients were less able to verbalize emotions than psychoneurotic patients, and also less able to modulate emotions, thus providing partial support for an association between alexithymia and IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, alexithymia is understood as a deficit in emotional and cognitive regulatory processes that are required for symbolic function, fantasy and empathy. Early studies, prior to the development of a psychometrically sound instrument, suggested a high prevalence of alexithymia in UC compared to irritable bowel syndrome [50]and psychoneurotic controls [51]and decreased verbal content on emotional tasks in UC and CD patients [52, 53]. A recent case-control study of 112 IBD patients using the validated Toronto Alexithymia Scale found a rate of alexithymia of 35.7%, significantly greater than the rate in healthy controls of 4.5% [54], and these alexithymia scores appear to be stable over time [55].…”
Section: Coping In Ibdmentioning
confidence: 99%
“…These other instruments are the Schalling-Sifneos Personality Scale [Apfel and Sifneos, 1979], the Thematic Appercep tion Test [Defourny et al, 1976/77;Taylor, 1981Taylor, , 1982, the MMPI alexithymia scale [Kleiger and Kinsman, 1980] and the archety pal 9 test [Demers-Desrosiers, 1982;Cohen et al, 1983].…”
Section: Discussionmentioning
confidence: 99%